Protective Effect of Aerial Parts Extract of Scrophularia Striata on Cadmium and Mercury-Induced Nephrotoxicity in Rat - M Zaheri (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: Most of these contaminants, by increased production of free radicals of oxygen, cause nephrotoxicity in human and experimental animals. Anti-oxidant structures existing in the medicinal plants are suitable candidates for protection against poisoning by these substances. In the present research, for the first time, the effect of the alcoholic juice of the aerial sections of scrophularia striata (Teshnehdaru) on nephrotoxicity caused by cadmium and mercury is investigated.METHODS: Forty two male Wistar rats (200-250 g) were randomly divided into 6 groups (n=7) to receive a daily corresponding dose of cadmium chloride (3mg/kg, i.p., group Cd), mercuric chloride (1.5mg/kg, i.p., group Hg), extract of Scrophularia striata (400 mg/kg, i.p., group Ss), combination extract and cadmium chloride (CS), combination extract and mercury chloride (HS) and normal saline as control (CT). At the end of the 8 day blood samples were collected and nephrotoxicity was evaluated by measuring serum urea, serum creatinine, blood urea nitrogen (BUN) and uric acid concentration. FINDINGS: Administration of hydroalcoholic extract of Scrophularia striata induced a significant decrease urea and uric acid compared with control group. Cd- induced increases in urea, creatinine, BUN and uric acid were significantly reduced by treatment with extract. In compared with control group in Hg group uric acid and creatinine increased but urea and BUN decreased. Treatment with extract improved nephrotoxicity. CONCLUSION: The results showed that scrophularia striata may have a protective effect against heavy metal induced nephrotoxicity.